Applying the Living Lab Methodology for Evidence-Based Educational Technologies - Moran-Mirabal, Luis F.; Ruiz-Ramirez, J. Alejandra; Gonzalez-Grez, Antonio A.; Torres-Rodriguez, Sergio N.; Ceballos, Hector G. (IEEE Global Engineering Education Conference, 2025)
Over the last two decades, 'Living Labs' have sprung around the globe as innovative and efficient research infrastructures, involving several stakeholders in a user-centered, iterative, open innovation ecosystem, where co-creation takes place in a real-life environment. Universities present a great opportunity for Living Labs, given that they have the infrastructure, technologies, and experienced academic staff for their implementation. Therefore, this paper presents the case of a Living Lab focused on Educational Technologies (EdTechs), the 'IFE Living Lab' (IFE-LL), as part of the Institute for the Future of Education at Tecnologico de Monterrey. The IFE-LL focuses on the evaluation, experimentation, and improvement of EdTechs through co-creation in a Living Lab environment. Throughout the paper, a description of the IFE-LL users, innovation process, cocreation and evaluation frameworks, and examples of successful projects is presented. The IFE-LL offers an innovation space for evidence-based educational technologies that links EdTech companies and startups, researchers, faculty members, and students, for the continuous improvement of EdTechs, development of academic and professional competences, creation and transfer of educational innovation knowledge, and collaboration in enriched and effective experiential teaching/learning environment.